The crisis in Latin America's integration process also reveal a crisis in integration law - Diaz Labrano, Roberto Ruiz (2009)
Opines that one of the expressions of weakness is evidenced in the functioning of organs or institutions for conflict resolution. Notes that the scope of their competencies are limited and their resolutions, in most cases, lack mechanisms to enforce them, all this added to the non-compliance of norms, which generates mistrust and insecurity.